Malay ethnobotany: natural colourants as eco-friendly dyes - Jamaludin, Nur Atiqah; Ramya, Razanah; Mat Ali, Qurratu Aini; Othman, Rashidi (Nova Science Publishers, Inc., 2024)
Natural dyes have been used since ancient times to colour food products, cosmetics, textiles, and pharmaceuticals. The recent ‘back to nature’ trend has increased the value and popularity of natural plant-based dyes. These natural and organic products offer several benefits: they are environmentally friendly, sustainable, and safe to use. The health and environmental advantages, along with the practicality of natural dyes, make them far more beneficial than synthetic colorants. In the food industry, natural colorants enhance the appearance of products, ensure consistent colouring, and replace synthetic colorants, which may have harmful health effects. In the cosmetics industry, to avoid the detrimental effects of harsh chemicals found in synthetic colorants, natural colorants are preferred for creating makeup shades, hair dyes, and personal care products. In the pharmaceutical industry, natural colorants help in colouring medications for easier identification and differentiation. In the textile industry, natural colorants are used to produce environmentally friendly clothing dyes. This paper explores the various plant-based pigments that the Malay community uses as natural dye colorants. Overall, choosing natural colorants over synthetic ones supports both environmental and human health.